2021
DOI: 10.5194/bg-2021-263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changing sub-Arctic tundra vegetation upon permafrost degradation: impact on foliar mineral element cycling

Abstract: Abstract. Arctic warming and permafrost degradation are modifying northern ecosystems through changes in microtopography, soil water dynamics, nutrient availability, and vegetation succession. Upon permafrost degradation, the release of deep stores of nutrients such as nitrogen and phosphorus from newly thawed permafrost stimulates Arctic vegetation production. More specifically, wetter lowlands show an increase in sedges (as part of graminoids), whereas drier uplands favor shrub expansion. In turn, shifts in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Betula nana was found to increase near-surface long-lived fine root biomass in a fertilization experiment (Sullivan et al, 2007), which could partially explain its successful eventual replacement of E. vaginatum (which has an annual root system) in long-term Arctic fertilization experiments (Shaver and Chapin, 1995;Shaver et al, 2001). Recent studies have suggested that initial uptake of nutrients by fast-growing graminoids and other deeply rooted forbs may move nutrients above-ground in the form of more quickly decomposing litter, where shrubs may then access it over longer time-scales (Wookey et al, 2009;Hewitt et al, 2019;Mauclet, Agnan, et al, 2021).…”
Section: A Natural Thermokarst Gradient Versus a Warming Experimentsmentioning
confidence: 99%
“…Betula nana was found to increase near-surface long-lived fine root biomass in a fertilization experiment (Sullivan et al, 2007), which could partially explain its successful eventual replacement of E. vaginatum (which has an annual root system) in long-term Arctic fertilization experiments (Shaver and Chapin, 1995;Shaver et al, 2001). Recent studies have suggested that initial uptake of nutrients by fast-growing graminoids and other deeply rooted forbs may move nutrients above-ground in the form of more quickly decomposing litter, where shrubs may then access it over longer time-scales (Wookey et al, 2009;Hewitt et al, 2019;Mauclet, Agnan, et al, 2021).…”
Section: A Natural Thermokarst Gradient Versus a Warming Experimentsmentioning
confidence: 99%
“…Non-vascular plant cover is dominated by mosses (mainly Sphagnum spp., Dicranum spp., and feather mosses including Hylocomium splendens and Pleurozium schreberi) and lichen species (e.g., Nephroma spp., Cladonia spp., and Flavocetraria cucullata) (Deane-Coe et al, 2015;Natali et al, 2012;Schuur et al, 2007). Since the start of the thermokarst development, vegetation cover changed with the evergreen and deciduous shrubs (as V. uliginosum and R. tomentosum), and forbs (as R. chamaemorus) being dominant at the expense of the sedges (Jasinski et al, 2018;Mauclet et al, 2021;Schuur et al, 2007;Villani et al, 2022).…”
Section: Study Area and Samplingmentioning
confidence: 99%